Gender- and age-related features of the association between TP53 Pro72Arg polymorphism and primary open-angle glaucoma - S.Iu. Mogilevskyy; S.V. Ziablitsev; L. I. Denisiuk (Journal of Ophthalmology, 2016)
Background: The TP53 gene is directly related to the development of primary open-angle glaucoma (POAG). There have been inconsistent reports regarding increased risk of POAG and the C allele (72Pro) of the TP53 codon 72 polymorphism.